2001
DOI: 10.1177/002215540104900211
|View full text |Cite
|
Sign up to set email alerts
|

The Murine Receptor for Urokinase-Type Plasminogen Activator Is Primarily Expressed in Tissues Actively Undergoing Remodeling

Abstract: uPAR is a cellular receptor for urokinase plasminogen activator, an enzyme involved in extracellular matrix degradation during processes involving tissue remodeling. We have expressed a recombinant soluble form of murine uPAR and raised rabbit polyclonal antibodies to study the expression of uPAR by immunohistochemistry. The immunohistochemical localization of uPAR was determined in normal mouse organs and in tumors formed by the highly metastatic Lewis lung carcinoma. uPAR immunoreactivity was found in the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 50 publications
4
100
1
Order By: Relevance
“…The murine uPAR antibody intensely stains the tumor vasculature (Figure 5b), consistent with other reports that uPAR expression is upregulated in endothelial cells during tissue remodeling, and is expressed in human glioma tumor vasculature. [34][35][36] Indeed, FACS analysis demonstrated high levels of uPAR in murine BCEC as has been shown previously for human brain microvascular cells. 37 A comparison of the level of neovascularization, as judged by CD31 expression, for the group receiving combined treatment with PEGh1-48 and PEGhm1-48 and control groups, was measured by immunohistochemistry and a representative example is shown in Figure 5c A quantitative analysis of tumor cell proliferation (Ki-67), apoptosis (TUNEL), and neovascularization (vessel counts) was then undertaken to further investigate the tumors observed in the treated groups, with the results shown in Table 3.…”
Section: Analysis Of Tumor Growth Inhibitionmentioning
confidence: 58%
“…The murine uPAR antibody intensely stains the tumor vasculature (Figure 5b), consistent with other reports that uPAR expression is upregulated in endothelial cells during tissue remodeling, and is expressed in human glioma tumor vasculature. [34][35][36] Indeed, FACS analysis demonstrated high levels of uPAR in murine BCEC as has been shown previously for human brain microvascular cells. 37 A comparison of the level of neovascularization, as judged by CD31 expression, for the group receiving combined treatment with PEGh1-48 and PEGhm1-48 and control groups, was measured by immunohistochemistry and a representative example is shown in Figure 5c A quantitative analysis of tumor cell proliferation (Ki-67), apoptosis (TUNEL), and neovascularization (vessel counts) was then undertaken to further investigate the tumors observed in the treated groups, with the results shown in Table 3.…”
Section: Analysis Of Tumor Growth Inhibitionmentioning
confidence: 58%
“…Expression was induced by 0.5 mM Cu 2 SO 4 for 7 days at 25°C, and in the case of pro-uPA the media also contained 10 g/ml aprotinin to prevent proteolytic cleavage at the activation site (29). muPAR and a selected number of single site mutants thereof were purified by immunoaffinity chromatography using an immobilized mouse monoclonal anti-uPAR antibody (KOR-1) raised against purified huPAR in a uPAR-deficient transgenic mouse (35). Studies by mass spectrometry using a protocol developed for huPAR (36) revealed that our purified muPAR preparation was heterogeneously glycosylated with roughly 25% carrying bi-antennary glycans on three sites, 50% on four sites, and 25% on five sites.…”
Section: Methodsmentioning
confidence: 99%
“…uPAR exhibits a limited expression pattern in nonmalignant cells (8), with notable exceptions including myeloid cells and their precursors (9), endothelial cells activated in support of angiogenesis (10), and smooth muscle cells that migrate into the neointima of atherosclerotic lesions (11). uPAR expression in fibroblasts is regulated by inflammatory mediators (12).…”
Section: Urokinase Receptor (Upar)mentioning
confidence: 99%